Leaching kinetics of metallic silver with sodium cyanide in hydrogen peroxide solution - Aydogan, Salih; Abdelraheem, Mohamed Taha Osman; Ali, Babiker; Boyrazli, Mustafa (Wiley, 2025)
This article describes the kinetics of dissolving pure metallic silver (Ag) in sodium cyanide with a hydrogen peroxide (H2O2) solution. The impacts of temperature, sodium cyanide concentration, rotation speed, and H2O2 concentration were investigated. The findings demonstrate that a favourable relationship exists between the rate of silver dissolution and the rotation speed. Moreover, sodium cyanide concentration of 0.0125 M was sufficient to dissolve silver. Hydrogen peroxide concentrations between 0.05 and 0.035 M have a significant impact on the dissolution rate; however, 0.050 M concentration had an adverse effect and resulted in the formation of a silver oxide layer. Temperatures between 20 and 55 degrees C have a positive influence because this range is where H2O2 is stable, but a temperature of 60 degrees C decreased the silver dissolution rate due to decomposition of hydrogen peroxide. A measurement of 21.50 kJ/mol was calculated of the activation energy.
Keywords: activation energy; cyanide; dissolution; hydrogen peroxide; silver